2011
DOI: 10.1007/s12028-011-9657-x
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Seizure Incidence in Thrombolysis-treated Ischemic Stroke Patients

Abstract: In this cohort of tPA-treated patients, post-stroke seizures were associated with atrial fibrillation and early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
3
31
1
Order By: Relevance
“…We did not find a treatment effect from the rate of TPA administration between the groups (p = 0.25). Other studies have also not identified a risk for patients to develop PSS following administration of recombinant TPA [44,45]. Currently, there are no specific evidence-based guidelines for medical management of PSS or strokerelated epilepsy beyond symptomatic treatment with ASDs.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a treatment effect from the rate of TPA administration between the groups (p = 0.25). Other studies have also not identified a risk for patients to develop PSS following administration of recombinant TPA [44,45]. Currently, there are no specific evidence-based guidelines for medical management of PSS or strokerelated epilepsy beyond symptomatic treatment with ASDs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have tried determining the relation between thrombolytic treatment and post-stroke epilepsy or seizures. The overall incidence rate of seizures in patients treated with r-tPA ranges from 4% to 20% [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several physiopathological mechanisms can be postulated for this association, including cortical reperfusion/hyperperfusion syndrome [3], neurotoxicity and a possible epileptogenic effect of rtPA [3][4][5][6], or the survival of islands of cortical viable tissue [7]. rtPA related seizures [3,8,9] and seizure frequency in patients treated with rtPA [10,11] have been mostly described using retrospective and non-controlled case series. Furthermore, the occurrence of seizures in rtPA patients has been associated with different stroke functional outcomes [1,3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…rtPA related seizures [3,8,9] and seizure frequency in patients treated with rtPA [10,11] have been mostly described using retrospective and non-controlled case series. Furthermore, the occurrence of seizures in rtPA patients has been associated with different stroke functional outcomes [1,3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%